The impact of attitude, subjective norms, and perceived behavioural control on managers’ intentions to behave ethically - Kashif, Muhammad; Zarkada, Anna K.; Thurasamy, Ramayah (My University, 2018)
This study employs a well-established psychosocial theory of a western, advanced economies-based model, that of the Extended Theory of Planned Behaviour, to study the intentions to behave ethically of Telecom and Bank managers. A researcher-administered paper-based survey was conducted among 484 managers working in banking and telecom organisations in Pakistan. The collected data were analysed by means of second-order confirmatory factor analysis. The results reveal three independent variables of attitude, subjective norms, and perceived behavioural control to strongly influence the ethical intentions of customer service managers. The relationship between customer service managers and their customers is more than anything else based on trust which cannot become established without not only an image of ethicality in the eyes of customers but also by clear demonstrations of ethical behaviours by frontline. The findings of this study are helpful in guiding customer service managers from banking and telecom sectors to foster an ethical workplace culture based on strengthening their staff sense of control and support in applying ethical norms. This is the first application of the extended Theory of Planned Behaviour model to predict ethical intentions of frontline customer service managers working in high-contact service organisations in a developing, Asian country.
Keywords: TPB; ethics; managers; SmartPLS; Pakistan